Self-administration of Methamphetamine Aerosol by Male and Female Baboons - Foltin, Richard W. (Pharmacol Biochem Behav, 2018)
The reinforcing efficacy of vaporized methamphetamine HCl (0.3 mg/kg) was determined in baboons with minimal previous drug exposure. A group of 8 adult male baboons was tested prior to a group of 7 adult female baboons. Baboons were initially trained to suck on a brass stem activating a pressure-sensitive relay (i.e., puff), to receive one M&M® candy. Five of the 8 males and 6 of the 7 females learned to activate the relay. 0.05 ml of 95% ethyl alcohol containing 0.3 mg/kg methamphetamine was vaporized and delivered to the mouth of the baboon after he/she completed 2 puffs; a single candy was given after an additional 5 puffs to ensure that baboons continued puffing after the aerosol entered their mouths. Puffing was recorded but not reinforced by candy or drug for 2 min after each aerosol delivery for males and 1 minute for females. Males could earn 10 and females could earn 20 aerosol deliveries. Males made between 225 and 650 puffs each session. Females made between 200 and 400 puffs each session. When only candy and placebo aerosol were delivered the number of puffs decreased in all 6 females but increased in all 5 males. When candy was delivered without aerosol, puffing decreased in 4 of 5 males, but this manipulation was not tested in females. Methamphetamine aerosol delivery maintained lower rates of puffing behavior in females than males, but procedural differences weaken interpretation of this sex comparison. Although training non-human primates to inhale drug vapors is time consuming, if successful, their long lifespan could provide years of valuable data justifying further work with non-human primates using models of vaporized drug self-administration.